Advanced papillary thyroid carcinoma responding to nivolumab. (March 2021) - Michel Ocampo, Miguel; Lerner, Jaren; Tosonian, Shawnt; Dasanu, Constantin A
Introduction: Clinical indications of immune checkpoint inhibitors have expanded to a variety of malignancies. Approximately one in six patients with hepatocellular carcinoma respond to programmed death 1 inhibitors nivolumab and pembrolizumab. Case report: We report herein a patient with synchronous metastatic hepatocellular carcinoma and advanced papillary thyroid carcinoma treated with nivolumab in the second-line therapy. Management and outcome: The hepatocellular carcinoma showed a durable response to the second-line agent nivolumab. Remarkably, the patient's papillary thyroid carcinoma also responded to this programmed death 1 inhibitor. Discussion: To our knowledge, this is the first case report showing the efficacy of nivolumab in the treatment of metastatic papillary thyroid carcinoma. Further studies with immune checkpoint inhibitors in papillary thyroid carcinoma seem warranted.